The relevance of the national education system in the educational thinking of Ki Hajar Dewantara - Indrayani, Nelly; Purnomo, Budi; Oktaniati, Ovi (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
The national education system must be able to guarantee human quality. Through education, human values are inherited. Today's condition of human values can be seen in various cases of violence, bullying, and educational persecution. This research contributes to revealing the relevance of today's national education in Ki Hajar Dewantara's educational thinking in the context of different times. The historical method is used by collecting data/literature and then conducting literature criticism. The next step is to do an interpretative and present a description describing the era's contextual education system. The results of this study indicate that there is historical continuity in the context of different times. Ki Hajar Dewantara's education system is dynamic and continuous with the national education system. The basic education system for Ki Hajar Dewantara is to build people who are faithful and pious. Ki Hajar Dewantara built an education system that upholds human values and has the right to education without discrimination. Meanwhile, national education provides equity in receiving education and is democratic.